2023
DOI: 10.32604/biocell.2023.030742
|View full text |Cite
|
Sign up to set email alerts
|

Fang-Xia-Dihuang decoction inhibits breast cancer progression induced by psychological stress via down-regulation of PI3K/AKT and JAK2/STAT3 pathways: An in vivo and a network pharmacology assessment

LINGYAN LV,
JING ZHAO,
XUAN WANG
et al.

Abstract: Background: The development and prognosis of breast cancer are intricately linked to psychological stress.In addition, depression is the most common psychological comorbidity among breast cancer survivors, and reportedly, Fang-Xia-Dihuang decoction (FXDH) can effectively manage depression in such patients. However, its pharmacological and molecular mechanisms remain obscure. Methods: Public databases were used for obtaining active components and related targets. Main active components were further verified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…It shows promise in treating various types of solid cancers [8]. Many studies have demonstrated that numerous bioactive compounds from natural plants or Chinese medicine have shown antitumor properties against multiple cancers by inhibiting the JAK2/STAT3 pathway in vivo and in intro [9][10][11]. Anthraquinone can hinder the growth and advancement of CC cells by targeting the JAK2/STAT3 signaling pathway [12].…”
Section: Introductionmentioning
confidence: 99%
“…It shows promise in treating various types of solid cancers [8]. Many studies have demonstrated that numerous bioactive compounds from natural plants or Chinese medicine have shown antitumor properties against multiple cancers by inhibiting the JAK2/STAT3 pathway in vivo and in intro [9][10][11]. Anthraquinone can hinder the growth and advancement of CC cells by targeting the JAK2/STAT3 signaling pathway [12].…”
Section: Introductionmentioning
confidence: 99%